Faktor Kesulitan Belajar Pada Mata Pelajaran Menggambar Busana Siswa Kelas XI SMK - Parwita, Ita; Sholikhah, Na’imatun (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2024)
The purpose of this study was to determine the factors of learning difficulties in the subject of fashion drawing. This type of research is quantitative descriptive research. Data collection techniques using questionnaires/questions, observation, and documentation. The data analysis technique uses descriptive statistical analysis techniques by calculating the Mean, Median, Mode, and Standard Deviation. The results showed that the factors for learning difficulties in fashion drawing were in the high category with a frequency of 41.67%. Data on the factors of learning difficulties in the subject of fashion drawing have two indicators, namely factors from within the student and factors from outside the student. Factors from within students are a very high category with a relative frequency of 81.25%. Factors from outside students are in the high category with a frequency of 41.67%. The study results concluded that factors from within the students must determine the difficulty of learning the subject of fashion drawing compared to factors from outside the students.